Synthesis and Characterization of Some Heterocyclic Compound Tetrazole from Schiff Base - Hala Shakier Lihames Al-Shimmery; Ferdos Sammie (Al-Qadisiyah Journal of Pure Science, 2017)
A series of five membered ring, the tetrazole have been synthesized via Schiff base with sodium azide in the -to give the following compounds: o55)C-presence dry acetone at(501- 10-Methyl-3,6-bis(5-phenyl-1H-tetrazol-1-yl)-4a,10-dihydroacridine2- 3,6-bis(5-(3,5-dimethylphenyl)-1H-tetrazol-1-yl)-10-methyl-4a,10-dihydroacridine.3- 3,6-Bis(5-(2-Bromophenyl)-1H-tetrazol-1-yl)-10-methyl-4a,10- dihydroacridine.4- 3,6-bis(5-(3-methoxy,5-hydroxyphenyl)-1H-tetrazol-1-yl)-10-methyl-4a,10-dihydroacridine.The derivatives have long been known to possess hypnotics activity and it is may be to get hypnotics activity from the newly prepared compounds.